The Effectiveness Of The Futsal Dribbling (FG) Training Model On Improving Dribbling Results For Beginners Players - Kurniawan, Febi; Natas Pasaribu, Ahmad Muchlisin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2021)
This study aims to determine the effectiveness of the dribbling training model of Febi Futsal games on improving the results of dribbling futsal for novice players. The research method used is descriptive quantitative research with experiments. A sample of 80 players was divided into 2 groups, with a purposive sampling technique. The instrument uses a modified dribbling test with a validity of 0.848 and a reliability of 0.906. The analysis technique used IBM SPSS for Windows 21 with normality test using Kolmogorof Smirnov with the results of the Asymp value. Sig (2-tailed) is greater than 0.05. While the homogeneity test used the Levene test with asymp results. sig (2-tailed) 5% or (p> 0.05). The analytical test used is the average difference test using the t-test analysis (Paired t-test). The results of the experimental group showed a significant difference of 0.00 <0.05, while the sig value of the control group was 0.00 <0.05. This shows that there is an increase in the results of exercise in both the experimental and control groups. The difference in the average increase between the experimental and control groups was 2.52> 0.81. There is a significant difference between the pre-test and post-test of dribbling practice, but the dribbling training model of febi futsal games for beginner players is more effective than the control group who practiced using conventional methods.